Pedagogic affect and its politics: learning to affect and be affected in education. Issue 1 (2nd January 2019) - Mulcahy, Dianne
ABSTRACT: This paper examines the critical contribution that affects as bodily capacities to act, engage and connect can make to children's learning in museums and schools. Drawing chiefly on empirical material collected over the course of visits by school children to Museums Victoria, Australia, and bringing a sociomaterial sensibility to bear, I trace the movements of these children through exhibition spaces and show pedagogic affect at work. I argue that children's learning can usefully be understood in ways that go beyond social constructivism which underwrites museum learning and school education yet tends to neglect the role of affectivity and material agency in learning, as well as relations of power. As the empirical material shows, the politics of affective practice involve the co-constitution of bodies, spaces and objects in ways that actively intervene in established relations of power. I conclude by calling for a renewed engagement with the affective in education.